Tren Penelitian Integrasi Budaya Lokal Indonesia dalam Pembelajaran di Sekolah (2022 – 2026): Analisis Bibliometrik - Hafida Rahma; Nisrina Azizah; Eko Handoyo (Indo Publishing, 2026)
This study aims to analyze research trends on the integration of local culture in school learning during the 2022–2026 period using a bibliometric approach with data sourced from the Scopus database through the keywords